Kajian Aplikasi Dron dalam Pengawalan Keselamatan Pekerja di Tapak Bina - Johan Adzhar, Nur Safirah; Kasim, Narimah; Ariffin, Ahmad Hamdan; Shapiai, Mohd Faiz (Research in Management of Technology and Business, 2023)
The construction industry is an important sector in driving the national economic development in Malaysia. However, emphasis on the importance of worker safety issues in the construction industry throughout Malaysia needs to be addressed. Although various acts, laws and regulations have been introduced by stakeholders but there are still accidents occurring on construction sites. Due to that, drone technology has the potential to reduce the rate of increase in accidents that occur during construction work. Therefore, this study was conducted to identify the potential, examine the main problems and steps to improve the application of drones in the control of worker safety at construction sites in the construction industry in Malaysia. Data was collected using a qualitative method using semi-structured interview questions with G7 contractors who were directly involved in controlling the safety of workers on construction sites. In Selangor, a total of 3026 G7 contractors registered in the construction sector and more than 50 respondents were contacted. However, only 4 respondents were interviewed. The findings revealed that the potential of drones in the control of worker safety is data collection. One of the primary challenges with drone applications is their resilience to present weather and endeavors to improve drone applications are initiatives of the Malaysian Digital Economy Corporation (MDEC). In conclusion, this study can enlighten those working in the construction sector on how drones might be used to manage worker safety concerns in Malaysia in the future.